Analysing the language used in resumes through discourse analysis for social intelligence - Mimi Nahariah Azwani Mohamed,; Muhammad Nadzrin Khairuddin,; Salawati Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
A resume is a tool for individuals to showcase their professional background and values to market themselves for employment. It is a technical written discourse that requires specific terms and language to convey specific information about job applicants. Recent trends show that recruiters have started looking for candidates with a high level of social intelligence. In order to get through the screening process, job applicants not only need to showcase their values, but also high level of social intelligence through their resume. Nevertheless, fresh graduates do not seem to be concerned about producing good and effective resumes. In many cases, graduates are found to simply copy paste the required information into a standard template. Within this context, it is vital for future graduates to produce effective resumes that provide clear information about them and at the same time demonstrate social intelligence to capture the attention of recruiters. This study examined the presence of social intelligence in written discourse, focusing on the career goal section of four resumes produced by four final year students of one technical university in Malaysia. The resumes were also examined by four human resource officers to obtain their opinions. The career goal section was examined through transactional and interactional functions of language. The findings generated from this analysis were then mapped against Albrecht’s of social intelligence dimensions, SPACE. Based on the mapping and the opinions of the human resource officers, it could be concluded that the language used to achieve transactional function of language can be associated with Clarity while language used to achieve interactional function of language can be associated with Situational Awareness. The study also highlighted that social intelligence can be identified in written discourse.